Species diversity of medically important necrophagous flies in Southwest Iran - Morteza Akbari; Javad Rafinejad; ‪Mahmoud Fazeli-Dinan; Ali-Ashraf Aivazi; Ali Jalilian; Soraya Sheikhi; Kamran Akbarzadeh (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Akbari M, Rafinejad J, Fazeli-Dinan M, Aivazi AA, Jalilian A, Sheikhi S, Akbarzadeh K. 2023. Species diversity of medically important necrophagous flies in Southwest Iran. Biodiversitas 24: 1467-1472. Species diversity of medically important necrophagous flies in Southwest Iran. Biodiversitas 24: 1467-1472. The insects are the most successful group in the phylum Arthropoda. Flies are among the most diverse group of insects and organisms. Flies can affect human health in many ways, such as the transmission of a wide range of pathogens and myiasis. Species diversity is the middle level of the hierarchical system of biodiversity. Flies, like other insects, are sensitive to biotic and abiotic factors, and their biodiversity will change under different climatic conditions. This study was performed in Ilam province, in southwest Iran. Two methods were used for collecting the flies, including bottle traps and insect nets. Fly collections were done monthly at each collection site for a year, and to identify the trapped flies, reliable identification keys were used. Calculation of fly species diversity indices was done based on the Shannon-Wiener index, species dominance based on the Simpson dominance index, species richness employing the Margalef's index, and evenness was performed based on the Evenness index. Different aspects of species diversity were calculated using PAST V.3 software. The dominance and abundance of necrophagous flies were higher in the south of the province. The highest evenness was related to the north of the province. A comparison of the diversity of necrophagous flies also indicated that the north of the province has a high species diversity. A significant and positive relationship between fly frequency and the temperature was seen. There was also a significant and negative relationship between the frequency of flies and humidity. The results of this study completed one of the research puzzles on the biodiversity of Iranian flies. The abundance and diversity of necrophagous flies were high in the Ilam province, especially in spring.